U-Form vs. M-Form: How to Understand Decision Autonomy Under Healthcare Decentralization?; Comment on "Decentralisation of Health Services in Fiji: A Decision Space Analysis" - Arturo Vargas Bustamante (Kerman University of Medical Sciences, 2016)
For more than three decades healthcare decentralization has been promoted in developing countries as a way of improving the financing and delivery of public healthcare. Decision autonomy under healthcare decentralization would determine the role and scope of responsibility of local authorities. Jalal Mohammed, Nicola North, and Toni Ashton analyze decision autonomy within decentralized services in Fiji. They conclude that the narrow decision space allowed to local entities might have limited the benefits of decentralization on users and providers. To discuss the costs and benefits of healthcare decentralization this paper uses the U-form and M-form typology to further illustrate the role of decision autonomy under healthcare decentralization. This paper argues that when evaluating healthcare decentralization, it is important to determine whether the benefits from decentralization are greater than its costs. The U-form and M-form framework is proposed as a useful typology to evaluate different types of institutional arrangements under healthcare decentralization. Under this model, the more decentralized organizational form (M-form) is superior if the benefits from flexibility exceed the costs of duplication and the more centralized organizational form (U-form) is superior if the savings from economies of scale outweigh the costly decision-making process from the center to the regions. Budgetary and financial autonomy and effective mechanisms to maintain local governments accountable for their spending behavior are key decision autonomy variables that could sway the cost-benefit analysis of healthcare decentralization.